Erratum: Influence of oxygen plasma treatment parameters on poly(vinylidene fluoride) electrospun fiber mats wettability - Correia, D. M. (2015)
Electrospun poly(vinylidene ﬂuoride) (PVDF) fiber mats find applications in an increasing number of areas, such as battery separators, filtration and detection membranes, due to their excellent properties. However, there are limitations due to the hydrophobic nature and low surface energy of PVDF. In this work, oxygen plasma treatment has been applied in order to modify the surface wettability of PVDF fiber mats and superhydrophilic PVDF electrospun membranes have been obtained. Further, plasma treatment does not significantly influences fiber average size (~400 ± 200 nm), morphology, electroactive -phase content (~80-85%) or the degree of crystallinity (Xc of 42 ± 2%), allowing to maintain the excellent physical-chemical characteristics of PVDF. Plasma treatment mainly induces surface chemistry modifications, such as the introduction of oxygen and release of fluorine atoms that significantly changes polymer membrane wettability by a reduction of the contact angle of the polymer fibers and an overall decrease of the surface tension of the membranes.